The Role of Public School Teachers in East Jerusalem in Mainstreaming Students with Special Needs - Khatib, Rula Nemir Faries Ganem (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to examin the role of teachers in supporting inclusive education for students with special needs in public schools in East Jerusalem, within the broader framework of promoting educational equity and inclusion. It aims to assess the current state of inclusion in regular classrooms, identify the key professional and structural challenges faced by teachers, and explore opportunities for enhancing inclusive practices in the complex sociopolitical context of Jerusalem.A descriptive-analytical methodology was employed, and data were collected through a structured questionnaire addressing three core dimensions: (1) teachers’ readiness, (2) the challenges they encounter, and (3) their daily practices with students with special needs. The sample consisted of 47 teachers selected through stratified random sampling from public schools in East Jerusalem. Findings revealed that 68% of the participants struggle to meet the diverse individual needs of students due to a lack of specialized training and limited supportive resources. Additionally, 84% emphasized the importance of psychosocial support as essential to successful inclusion, while 75% indicated that their schools lack effective inclusive environments. Despite these obstacles, most teachers expressed a positive educational awareness regarding the value of inclusion and its impact on students’ social and academic development. The study recommends strengthening teacher preparation programs in inclusion, ensuring continuous professional and psychological support, and adopting differentiated instructional strategies to foster inclusive school environments in East Jerusalem.
Keywords: inclusion; special needs; teacher role; inclusive education; East Jerusalem